Handbook of logic in computer science. - Abramsky, Samson, 1953-; Gabbay, Dov M., 1945-; Maibaum, Thomas S. E., 1947- (Clarendon Press ; Oxford University Press, 2000)
This handbook volume covers fundamental topics of semantics in logic and computation. The chapters (some monographic in length), were written following years of co-ordination and follow a thematic point of view. The volume brings the reader up to front line research, and is indispensable to any serious worker in the areas.
Keywords: Computer science.; Logic, Symbolic and mathematical.; Electronic Data Processing; Informatique.; Logique symbolique et mathématique.; COMPUTERS -- Reference.; COMPUTERS -- Machine Theory.; COMPUTERS -- Computer Literacy.; COMPUTERS -- Information Technology.; COMPUTERS -- Data Processing.; COMPUTERS -- Computer Science.; COMPUTERS -- Hardware -- General.; Computer science; Logic, Symbolic and mathematical; Ciencia da computacao ou informatica.; Logica e semantica de programacao.; Programming.